2018 IEEE International Conference on Communications Workshops (ICC Workshops) 2018
DOI: 10.1109/iccw.2018.8403493
|View full text |Cite
|
Sign up to set email alerts
|

Underlay Control Signaling for Ultra-Reliable Low-Latency IoT Communications

Abstract: Future mobile networks not only envision enhancing the traditional link quality and data rates of mobile broad band (MBB) links, but also development of new control channels to meet the requirements of delay sensitive use cases. In particular, the need for ultra-reliable low-latency communications (URLLC) for many internet of things (IoT) users is greatly emphasized. In this paper, we present a novel spread spectrum waveform design that we propose for transmission of control signals to establish URLLC communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Wireless Communications and Mobile Computing next IoT paradigms [30]. In this context, the joint use of lossy compression and error correction coding is a key approach to deal with the twofold requirements, i.e., energy and reliability.…”
Section: Related Workmentioning
confidence: 99%
“…Wireless Communications and Mobile Computing next IoT paradigms [30]. In this context, the joint use of lossy compression and error correction coding is a key approach to deal with the twofold requirements, i.e., energy and reliability.…”
Section: Related Workmentioning
confidence: 99%
“…Cyclic prefix direct sequence spread spectrum (CP-DSSS) is a novel spread spectrum waveform that has been recently proposed [1]- [6] and has the potential of solving some of the key objectives of ultra-reliable low latency communications (URLLC) and massive machine type communications (mMTC) that have been noted in 5G NR but reliable solutions to them still to be explored/found.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] and [2], CP-DSSS was introduced as a secondary signaling method for sending a small number of control bits within each OFDM symbol interval concurrent with other communication signals within the network to enable resource allocation for URLLC communications. In [3], the feasibility of this signaling method in a 3GPP proposed industrial setting was explored and its reliable performance was further confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research on improving QoE of IoT SOs has attracted more and more attention [20][21][22]. Aminjavaheri et al [20] presented an underlay control signaling method for ultra-reliable low-latency communication applications in an LTE network and analyzed its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research on improving QoE of IoT SOs has attracted more and more attention [20][21][22]. Aminjavaheri et al [20] presented an underlay control signaling method for ultra-reliable low-latency communication applications in an LTE network and analyzed its performance. Since the satisfaction of QoE becomes the major challenge in content-centric IoT, the authors in [21] have analyzed lots of factors, i.e., content popularity and weight factor, which impact the resource allocation and how they subsequently influence the QoE.…”
Section: Introductionmentioning
confidence: 99%